Clinical and histopathological evaluation of cutaneous angiofibromas. (4th June 2021) - Nasimi, Maryam; Kamyab, Kambiz; Moradi, Arezou; Dasdar, Shayan; Kianfar, Nika
Abstract: Background: Angiofibromas are common benign skin lesions that are diagnosed clinically and histopathologically. Fibrous papule (FP) is one of the clinical types of angiofibromas located primarily on the nose. Methods: The cases with the confirmed diagnosis of angiofibroma were enrolled. Demographic features of the patients and clinical characteristics of the lesions were extracted. Moreover, histopathological features of the available slides were microscopically reviewed. Results: From 83 cases of cutaneous angiofibromas, 57 (69%) had lesions consistent with FP. The mean age at diagnosis was 37.7 ± 16.3 years and the most common site of involvement was the nose (53% of cases). Regarding the histopathological evaluation of 71 slides, most cases represented vascular changes (97%) and dermal fibroplasia (87%). Melanin incontinence (41%), acanthosis (31%), and lichenoid features (25%) were other common histopathological findings. Moreover, a sparse inflammatory cell infiltrate was present in 68% of cases. The most prevalent inflammatory cells were lymphocytes (61%) and histiocytes (34%). Conclusion: This study presented the histopathological findings of a series of cutaneous angiofibromas. Dermatopathologists should be aware of these features, especially those that are less common, to better diagnose and differentiate them from malignant neoplasms.